Ball speed and release consistency predict pitching success in Major League Baseball - Whiteside, D.; Martini, D. N.; Zernicke, R. F.; Goulet, G. C. (The Journal of Strength and Conditioning Research, 2016)
This study aimed to quantify how ball flight kinematics (i.e., ball speed and movement), release location, and variations therein relate to pitching success in Major League Baseball (MLB). One hundred ninety starting MLB pitchers met the inclusion criteria for this study. Ball trajectory information was collected for 76,000 pitches and inserted into a forward stepwise multiple regression model, which examined how (a) pitch selection, (b) ball speed, (c) ball movement (horizontal and lateral), (d) release location (horizontal and lateral), (e) variation in pitch speed, (f) variation in ball movement, and (g) variation in release location related to pitching success (as measured by fielding independent pitching—FIP). Pitch speed, release location variability, variation in pitch speed, and horizontal release location were significant predictors of FIP and, collectively, accounted for 24% of the variance in FIP. These findings suggest that (a) maximizing ball speed, (b) refining a consistent spatial release location, and (c) using varied pitch speeds should be primary foci for the pitching coach. However, between-pitcher variations underline how training interventions should be administered at the individual level, with consideration given to the pitcher's injury history. Finally, despite offering significant predictors of success, these three factors explained only 22% of the variance in FIP and should not be considered the only, or preeminent, indicators of a pitcher's effectiveness. Evidently, traditional pitching metrics only partly account for a pitcher's effectiveness, and future research is necessary to uncover the remaining contributors to success.